Preparation method of self-cleaning radiopharmaceutical filter membrane
By using a multi-layered composite filter membrane and employing techniques such as chemical affinity and ultrasonic vibration, the problem of traditional filter membranes being unable to effectively remove nanoscale radioactive contaminants has been solved, achieving efficient and safe purification and self-cleaning of radiopharmaceuticals.
Patent Information
- Application Number
- CN202511360716.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-23
- Publication Date
- 2026-01-23
AI Technical Summary
Existing filter membranes cannot effectively remove nanoscale or ionic radioactive contaminants such as free pertechnetate, resulting in substandard drug purification. Furthermore, traditional filter membranes are prone to clogging, increasing the risk of radiation exposure for patients.
The filter membrane employs a multi-layer composite structure, including a PTFE base membrane, a ZrO2-QCS composite layer, an Fe3O4 layer, and a PZT-PDMS encapsulation layer. It achieves specific adsorption and cleaning of free pertechnetate through chemical affinity, electrostatic interaction, and ultrasonic vibration.
It improves the selective removal of free pertechnetate, reduces drug residues, extends filter membrane life, reduces the risk of cross-contamination, and enhances operational safety and filtration efficiency.
Smart Images

Figure CN121372075A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of drug filtration membrane technology, and in particular to a method for preparing a self-cleaning radiopharmaceutical filter membrane. Background Technology
[0002] In the preparation of radiopharmaceuticals, filter membranes, as a key purification component, must efficiently remove small-molecule radioactive contaminants, such as free pertechnetate, to ensure the safety and efficacy of the drug. However, existing technologies have significant limitations: traditional filter membranes rely on physical pore size sieving mechanisms, primarily targeting bacteria (approximately 1 μm in size) or large particulate impurities, but have almost no retention capacity for nanoscale or ionic substances (such as free pertechnetate, with a hydrated diameter of approximately 0.5 nm). Furthermore, technetium-99m-labeled drugs (such as 99mTc-MIBI) are themselves small molecules or colloidal complexes (molecular weight 500 Da or particle size 10-100 nm), with sizes close to the lower limit of ordinary filter membrane pore size (0.22 μm), making it difficult to separate the drug from the contaminants. This contradiction in physical properties results in traditional filter membranes performing poorly in terms of adsorption efficiency, selectivity, and anti-clogging ability, failing to meet the stringent requirements of high precision and low residue in radiopharmaceutical purification. More seriously, incompletely removed free technetium peroxide can enter the body with the drug, causing additional radiation to non-target tissues (such as the thyroid and stomach) because it cannot target the lesion. Its half-life is 6 hours, increasing the risk to patients.
[0003] Therefore, it is necessary to provide a method for preparing a self-cleaning radiopharmaceutical filter membrane to solve the above-mentioned technical problems. Summary of the Invention
[0004] This invention overcomes the shortcomings of the prior art and provides a method for preparing a self-cleaning radiopharmaceutical filter membrane.
[0005] To achieve the above objectives, the technical solution adopted by the present invention is as follows: a method for preparing a self-cleaning radiopharmaceutical filter membrane, comprising the following steps:
[0006] S1: Place the porous PTFE membrane in an oxygen plasma cleaner to generate surface hydroxyl groups. Immerse the activated membrane in a 0.5-2% PVP aqueous solution for 5-15 minutes to allow PVP to be uniformly adsorbed onto the membrane surface. Then dry it at 40-80℃ for 2-3 hours to form a PTFE base membrane.
[0007] S2: Disperse ZrO2 nanoparticles in anhydrous ethanol and sonicate for 15-60 min to prepare a dispersion. Load ZrO2 onto the surface of a PTFE membrane by impregnation. Stir magnetically at 40-80℃ for 5-7 h. Finally, vacuum dry and cure at 80-160℃ for 1-2 h to form a uniform ZrO2 layer.
[0008] S3: reacting chitosan with EPTAC at 70-90 DEG C for 18-30 hours to generate QCS, removing unreacted reagents by using a dialysis bag with a molecular weight cut-off of 10,000 Da, freeze-drying to obtain QCS powder, dissolving the QCS in water to prepare a 1-3% solution, spraying the solution onto the surface of the ZrO2 layer, crosslinking using a glutaraldehyde solution, and forming a ZrO2-QCS composite layer;
[0009] S4: dissolving FeCl3*6H2O and FeSO4*7H2O in water at a molar ratio of 1.8-2.2:1, adjusting the pH to 10.5-11.5 at 80-90 DEG C, stirring to generate Fe3O4 nanoparticles, depositing the Fe3O4 suspension on the surface of the QCS layer by vacuum filtration to form a dense layer with a thickness of 4-6 microns, and drying at 50-70 DEG C for 1-2 hours to solidify the Fe3O4 layer;
[0010] S5: symmetrically pasting PZT pieces with a diameter of 8-12 mm on the edges of the PTFE film, fixing using epoxy resin glue, coating 0.8-1.2 mm thick polydimethylsiloxane (PDMS) on the surface of the PZT to form a PZT-PDMS packaging layer, and then connecting an external high-frequency signal generator to trigger ultrasonic vibration, wherein when self-cleaning, the PZT drives the PDMS layer to generate ultrasonic waves in combination with the catalytic action of Fe3O4;
[0011] S6: laminating the PTFE base film, the ZrO2-QCS composite layer, the Fe3O4 layer, and the PZT-PDMS packaging layer in sequence, fixing using a hot pressing method, and finally immersing the filter membrane in a pH 7.0 PBS buffer solution for 20-30 hours.
[0012] In one preferred embodiment of the present application, in the S1, the pore size of the PTFE film is 0.22 microns, the thickness is 100 microns, the porosity is 80%, the oxygen flow range of the oxygen plasma cleaning machine is 30-60 sccm, the power range is 80-150 W, and the processing time range is 3-10 minutes.
[0013] In one preferred embodiment of the present application, in the S2, the particle size of the ZrO2 nanoparticles is 20-50 nm, the concentration of the dispersion liquid is in the range of 5-15 mg / mL, and the immersion frequency is 2-3 times.
[0014] In one preferred embodiment of the present application, in the S3, the degree of deacetylation of chitosan is not less than 85%, and the mass ratio of EPTAC to chitosan is 1:1-1:6.
[0015] In a preferred embodiment of the present application, in the S3, the QCS spraying adopts a spray gun pressure of 0.2-0.5 MPa, a spraying distance of 10-15 cm, a spraying rate of 0.5-1.0 mL / min, and a cross-linking time of 1-2 h using 2-5% glutaraldehyde solution, followed by 3-5 times of water flushing.
[0016] In a preferred embodiment of the present application, in the S4, the particle size of the Fe3O4 nanoparticles ranges from 100-200 nm, and the magnetic response strength is greater than 50 emu / g.
[0017] In a preferred embodiment of the present application, in the S4, the concentration of the Fe3O4 suspension ranges from 10-20 mg / mL, the vacuum filtration pressure ranges from 0.05-0.1 MPa, and the time ranges from 10-30 min.
[0018] In a preferred embodiment of the present application, in the S5, the thickness of the PZT sheet ranges from 0.5-1.0 mm, and the mass ratio of the PDMS prepolymer to the curing agent is 11:1-9:1.
[0019] In a preferred embodiment of the present application, in the S5, the vibration frequency of the high-frequency signal generator ranges from 15-30 kHz, and the voltage ranges from 20-80 V; the ultrasonic vibration frequency during self-cleaning ranges from 15-25 kHz, and the voltage ranges from 40-60 V; and the trigger time ranges from 10-60 s.
[0020] In a preferred embodiment of the present application, in the S6, the hot-pressing temperature ranges from 120-160℃, the hot-pressing pressure ranges from 0.2-0.6 MPa, and the hot-pressing time is 10-30 s.
[0021] The present application solves the defects in the background art and has the following beneficial effects:
[0022] (1) The present application provides a preparation method of a self-cleaning radioactive drug filter membrane. Through the ZrO2-QCS composite layer formed in the S3, specific adsorption of free pertechnetate is achieved using chemical affinity, without significantly affecting the permeability of labeled drug molecules or colloidal complexes. This specific adsorption mechanism not only improves the selective removal capacity of target pollutants, but also ensures that the active ingredients of the drug preparation can smoothly pass through the filter membrane, ensuring the treatment effect.
[0023] (2) The application provides a preparation method of a self-cleaning radioactive drug filter membrane, and the traditional filter membrane is difficult to effectively separate the small molecular anions from the solution because the pore diameter of the traditional filter membrane is much larger than the hydration diameter of the free pertechnetate ion; in contrast, the application introduces a ZrO2 layer and a Fe3O4 layer with a uniform distribution of nanometers, which can effectively reduce the actual effective filter pore diameter and enhance the physical interception ability of small molecular substances.
[0024] (3) The application provides a preparation method of a self-cleaning radioactive drug filter membrane, and the PZT-PDMS encapsulation layer in S5 is arranged to promote the falling and dispersion of impurities on the surface of the filter membrane through ultrasonic vibration, reduce the risk of radioactive residue and cross contamination. This self-cleaning mechanism not only prolongs the service life of the filter membrane and reduces the replacement frequency, but also greatly improves the safety guarantee level of the operator, so that the whole filtering process is more efficient. BRIEF DESCRIPTION OF DRAWINGS
[0025] In order to more clearly illustrate the technical solutions in the embodiments of the application or the prior art, the following will briefly introduce the drawings needed to be used in the embodiment or prior art description. Obviously, the drawings described below are only some embodiments of the application, and for those skilled in the art, other drawings can be obtained without creative labor on the basis of these drawings;
[0026] Figure 1 is a flow schematic structure diagram of the preferred embodiment of the application. DETAILED DESCRIPTION
[0027] The technical solutions in the embodiments of the application will be described clearly and completely below with reference to the drawings in the embodiments of the application. Obviously, the described embodiments are only some of the embodiments of the application, not all. Based on the embodiments in the application, all other embodiments obtained by those skilled in the art without creative labor are within the protection scope of the application.
[0028] In the following description, many specific details are set forth in order to provide a thorough understanding of the application, but the application can also be implemented in other ways different from those described herein, therefore, the protection scope of the application is not limited by the specific embodiments disclosed below.
[0029] As Figure 1 shown, the application provides a preparation method of a self-cleaning radioactive drug filter membrane, including the following steps:
[0030] S1: A porous PTFE membrane with a pore size of 0;22 μm, a thickness of 100 μm and a porosity of 80% is placed in an oxygen plasma cleaning machine and treated for 3-10 min under the conditions of an oxygen flow of 30-60 seem and a power of 80-150 W to significantly improve the chemical activity and hydrophilicity of the membrane surface by generating a large number of surface hydroxyl groups; this surface activation not only enhances the adhesion between the membrane material and the subsequent coating layer, reducing the risk of delamination or peeling, but also provides more reaction sites for subsequent PVP adsorption; then, the activated membrane is immersed in a PVP aqueous solution with a concentration of 0:5-2% for 5-15 min, allowing PVP to be uniformly adsorbed on the membrane surface, and then dried at 40-80°C for 2-3 h to form a stable PTFE base membrane;
[0031] It should be noted that PVP, as a polymer with good biocompatibility and hydrophilicity, not only enhances the hydrophilicity of the membrane surface, reducing the water contact angle and thus reducing the resistance caused by hydrophobicity during filtration, but also improves the adsorption capacity of the membrane surface for subsequent functional layers such as ZrO2 nanoparticles;
[0032] In summary, the PTFE base membrane formed after S1 treatment has significantly enhanced surface activity and hydrophilicity, laying a solid foundation for subsequent construction of a functional layer that efficiently adsorbs free pertechnetate, and improving the selectivity and removal efficiency of the entire filter membrane system for target pollutants.
[0033] S2: First, ZrO2 nanoparticles with a particle size of 20-50 nm are uniformly dispersed in anhydrous ethanol, and a stable dispersion solution with a concentration of 5-15 mg / mL is prepared by ultrasonic treatment for 15-60 min to ensure good dispersibility of the nanoparticles in the solvent and avoid agglomeration; then, the dispersion solution is loaded onto the surface of the PTFE membrane that has been activated and coated with PVP using the immersion method, and is magnetically stirred at 40-80°C for 5-7 h to allow the ZrO2 nanoparticles to firmly adhere to the membrane surface and form a uniform and dense functional layer; repeating the immersion 2-3 times further enhances the loading capacity of ZrO2 and the adsorption efficiency for target pollutants; then, vacuum drying and solidification are performed at 80-160°C for 1-2 h to not only remove residual solvents but also form stable chemical bonding and physical crosslinking structures between the ZrO2 nanoparticles and the base membrane;
[0034] It should be noted that the ZrO2 functional layer formed after the above treatment significantly improves the specific adsorption capacity of the filter membrane for free pertechnetate; since ZrO2 nanoparticles have excellent cation exchange capacity and high affinity for TcO4 -The coordination bonding characteristics of QCS can effectively capture free pertechnetate ions, overcoming the problem that traditional physical interception mechanisms are ineffective for small molecule ions; the uniform distribution and multiple impregnation of the enhanced ZrO2 layer increase the actual effective filtration area, improving the selectivity and removal efficiency of the target pollutants;
[0035] In addition, the high-temperature treatment of vacuum drying solidification helps to remove residual solvents, prevent moisture or other impurities from affecting the performance of the filter membrane, and enhance the durability and reliability of the entire filter membrane system; This not only solves the technical problem of difficult removal of free pertechnetate, but also provides a solid foundation for subsequent construction of QCS composite layers and other functional layers, ultimately achieving efficient and highly selective purification of radiopharmaceuticals.
[0036] S3: Chitosan with a degree of deacetylation not less than 85% is reacted with EPTAC at a mass ratio of 1:1-1:6 at 70-90°C for 18-30h to synthesize QCS, so that the amino groups on the chitosan molecular chain are quaternized, giving it a stronger positive charge density; Subsequently, a dialysis bag with a molecular weight cut-off of 10,000 Da is used to remove unreacted reagents, and pure QCS powder is obtained by freeze-drying to ensure the high purity and stability of the final product and avoid the influence of unreacted substances on subsequent applications; Then, the obtained QCS powder is prepared into an aqueous solution with a concentration of 1-3%, and is uniformly sprayed onto the surface of the ZrO2 layer at a pressure of 0:2-0:5 MPa, a distance of 10-15 cm, and a rate of 0:5-1:0 mL / min. The uniformity and thickness of the QCS coating are ensured by controlling the spraying parameters, thereby enhancing the overall performance of the functional layer; After spraying, 2-5% glutaraldehyde solution is used for crosslinking for 1-2h to further fix the QCS layer, making it more stable and not easy to fall off; Finally, the unreacted glutaraldehyde and other impurities are removed by washing with water for 3-5 times to form a ZrO2-QCS composite layer, ensuring the quality and biocompatibility of the coating;
[0037] It should be noted that the ZrO2-QCS composite layer formed after S3 processing significantly improves the adsorption efficiency and selectivity of the filter membrane for free pertechnetate; Specifically, QCS has abundant positive charges, which can efficiently capture negatively charged TcO4 - ions through electrostatic interaction, and the ZrO2 layer mainly relies on the adsorption mechanism of coordination bonding;
[0038] In addition, the QCS also has good biocompatibility and antibacterial performance, improving the safety and practicality of the entire filter membrane system; the combination of the QCS layer and the ZrO2 layer forms a synergistic effect: ZrO2 provides specific chemical adsorption sites, while QCS enriches target ions through electrostatic interaction, and the two work together to significantly improve the retention rate of free pertechnetate; at the same time, glutaraldehyde crosslinking not only enhances the mechanical strength and durability of the coating, but also prevents the QCS layer from dissolving or falling off during long-term use, ensuring the long-term stability of the filter membrane; in summary, step S3 significantly improves the selectivity and removal efficiency of the filter membrane system for free pertechnetate by constructing a ZrO2-QCS composite layer.
[0039] S4: FeCl3·6H2O and FeSO4·7H2O are dissolved in water in a molar ratio of 1.8-2.2:1, the pH is adjusted to 10:5-11:5 at 80-90°C, and the Fe3O4 nanoparticles with a particle size range of 100-200 nm and a magnetic response strength greater than 50 emu / g are generated by stirring the reaction, which can ensure the uniformity and high magnetic response of the Fe3O4 nanoparticles, thereby improving their capture capacity for pollutants and the convenience of subsequent processing; then, the obtained Fe3O4 suspension (concentration of 10-20 mg / mL) is deposited on the surface of the QCS layer by vacuum filtration (pressure range of 0.05-0.1 MPa, time range of 10-30 min) to form a dense Fe3O4 layer with a thickness of 4-6 μm; the vacuum filtration technique can ensure that the Fe3O4 nanoparticles are uniformly and tightly attached to the substrate to form a continuous functional layer, which not only ensures the mechanical strength and stability of the Fe3O4 layer, but also avoids the problem of reduced filtration efficiency caused by gaps between particles; finally, drying at 50-70°C for 1-2h for solidification to further enhance the adhesion between the Fe3O4 layer and the underlying QCS layer, and to remove residual moisture to ensure the stability and durability of the entire composite membrane structure;
[0040] It should be noted that the FexO4 functional layer formed after S4 processing significantly improves the overall performance of the filter membrane system, especially in adsorbing and removing free pertechnetate; Fe3O4 nanoparticles have a large specific surface area and abundant active sites, which can effectively capture and fix free pertechnetate through physical adsorption and redox, supplementing the adsorption mechanism of ZrO2 and QCS layers, and further improving the retention rate of target pollutants;
[0041] In addition, Fe3O4 nanoparticles have excellent magnetic response, enabling the filter membrane to be quickly separated and recovered under the action of an external magnetic field, simplifying the processing flow of radioactive waste and reducing the risk of environmental pollution; vacuum filtration and drying solidification enable the Fe3O4 layer to be firmly attached to the surface of the QCS layer, forming a solid and continuous functional layer that enhances the durability and reliability of the entire filter membrane system in practical applications; the Fe3O4 layer and the underlying ZrO2-QCS composite layer work together to achieve a multi-stage adsorption mechanism for free pertechnetate ions - from coordination bonding to electrostatic adsorption to physical entrapment, significantly improving the selectivity and removal efficiency of the filter membrane.
[0042] S5: Paste a PZT sheet with a diameter of 8-12 mm and a thickness of 0:5-1:0 mm on the edge of the PTFE membrane at a symmetrical position, and use epoxy resin glue to fix it. The PZT sheet serves as a piezoelectric material that can generate mechanical vibrations when a voltage is applied. Then, coat a PDMS prepolymer with a thickness of 0;8-1;2 mm on the surface of the PZT. The mass ratio of PDMS prepolymer to curing agent is 11:1 to 9:1, forming a PZT-PDMS encapsulation layer. PDMS not only has good flexibility and biocompatibility, but also effectively protects the PZT sheet from external environmental influences, ensuring its long-term stable operation. Connect an external high-frequency signal generator and set the vibration frequency to 15-30 kHz and the voltage to 20-80 V. When self-cleaning is needed, trigger ultrasonic vibration with a vibration frequency of 15-25 kHz and a voltage of 40-60 V for a duration of 10-60 seconds. This precisely controlled ultrasonic vibration can drive the PDMS layer to oscillate at a high frequency, effectively loosening and removing impurities and pollutants attached to the surface of the filter membrane. Combined with the magnetic response characteristics of the Fe3O4 layer and its Fenton-like catalytic effect, ultrasonic vibration can further promote the oxidation-reduction degradation of pollutants by Fe3O4 particles.
[0043] It should be noted that the PZT-PDMS encapsulation layer formed after S5 processing significantly improves the overall performance and service life of the filter membrane. Controlled ultrasonic vibration can effectively remove deposits and pollutants from the surface of the filter membrane, reducing the risk of filter membrane clogging and extending the service life of the filter membrane.
[0044] At the same time, the need for manual cleaning is reduced, and maintenance costs are lowered. The PDMS encapsulation layer not only provides good protection against physical damage or chemical corrosion of the PZT sheet, but also enhances the mechanical strength and durability of the entire system, ensuring long-term stable operation. The combination of the Fe3O4 layer and ultrasonic vibration utilizes both physical vibration and chemical catalysis mechanisms, significantly improving the removal efficiency of pollutants, especially small molecule ions that are difficult to remove by traditional filtration methods, such as free pertechnetate ions. This synergistic effect is particularly pronounced.
[0045] S6: The PTFE base film, ZrO2-QCS composite layer, Fe3O4 layer and PZT-PDMS encapsulation layer are laminated in sequence, and fixed by hot pressing; the hot pressing temperature is set to 120-160°C, the pressure is 0.2-0.6 MPa, and the time is 10-30 seconds. The controlled hot pressing conditions ensure firm bonding between the layers, avoid the risk of delamination or falling off, and enhance the mechanical strength and stability of the entire filter membrane. Then, the laminated and fixed filter membrane is immersed in a phosphate buffer solution (PBS) with pH 7.0 for 20-30 h to simulate the physiological conditions in the actual application environment, which not only helps to release internal stress, but also improves the adaptability and long-term stability of the filter membrane in actual use.
[0046] It should be noted that the hot pressing process makes the PTFE base film, ZrO2-QCS composite layer, Fe3O4 layer and PZT-PDMS encapsulation layer tightly combined to form a filter membrane system with strong integrity and stable structure, which enhances the mechanical strength and reduces the risk of functional failure caused by physical wear or chemical corrosion; the PTFE base film provides good basic support; the ZrO2-QCS composite layer realizes efficient and specific adsorption of free pertechnetate; the Fe3O4 layer further enhances the removal efficiency of pollutants through magnetic response and catalytic effect.
[0047] The PZT-PDMS encapsulation layer gives the filter membrane an intelligent self-cleaning function, thereby improving the selectivity and removal efficiency of the filter membrane; the PBS buffer solution balancing treatment not only verifies the biocompatibility of the filter membrane, but also simulates the physiological conditions in the actual application environment to ensure that the filter membrane does not cause adverse reactions when it comes into contact with human tissues, which is particularly important for the preparation and use of radioactive drugs; in addition, the PZT-PDMS encapsulation layer combined with an external high-frequency signal generator realizes the intelligent self-cleaning function of the filter membrane, simplifies the maintenance process, reduces the need for manual cleaning, and prolongs the service life of the filter membrane.
[0048] Example One
[0049] S1: A porous PTFE membrane with a pore size of 0.22 μm, a thickness of 100 μm and a porosity of 80% is cut to the required size, and the cut PTFE membrane is placed in an oxygen plasma cleaning machine and treated under the conditions of oxygen flow 45 sccm and power 120 W for 7 min to generate a large number of active hydroxyl groups on the surface; then the activated membrane is immersed in a 1% PVP aqueous solution for 10 min to make PVP uniformly adsorbed on the membrane surface; and dried at 60°C for 2.5 h to form a PTFE base film;
[0050] S2: ZrO2 nanoparticles with a particle size of 35 nm were dispersed in anhydrous ethanol and ultrasonically treated for 30 min to obtain a dispersion liquid with a concentration of 10 mg / mL; the dispersion liquid was loaded onto the surface of the PTFE membrane by the immersion method, and was magnetically stirred at 60°C for 6 h to ensure uniform distribution of the nanoparticles; the nanoparticles were vacuum dried and solidified at 120°C for 1.5 h to form a uniform and dense ZrO2 functional layer; the immersion was repeated twice to enhance the loading amount;
[0051] S3: Chitosan with a degree of deacetylation of 90% was reacted with EPTAC at a mass ratio of 1:3 at 80°C for 24 h to synthesize QCS, and a dialysis bag with a molecular weight cut-off of 10,000 Da was used to remove unreacted substances, and QCS powder was obtained by freeze-drying; QCS was prepared into a 2% aqueous solution; the ZrO2 layer surface was sprayed using an airbrush at a pressure of 0.3 MPa, a distance of 12 cm, and a rate of 0.8 mL / min; then crosslinked with 3% glutaraldehyde solution for 1.5 h, and then washed with water for 4 times to form a ZrO2-QCS composite layer;
[0052] S4: FeCl3·6H2O and FeSO4·7H2O were dissolved in water at a molar ratio of 2:1, and the pH was adjusted to 11 at 85°C to generate Fe3O4 nanoparticles (particle size about 150 nm, magnetic response strength about 60 emu / g); the obtained suspension (concentration 15 mg / mL) was deposited on the surface of the QCS layer by vacuum filtration (pressure 0.075 MPa, time 20 min) to form a dense Fe3O4 layer with a thickness of 5 μm; the Fe3O4 layer was dried at 60°C for 1.5 h to solidify;
[0053] S5: A PZT sheet with a diameter of 10 mm and a thickness of 0.75 mm was symmetrically pasted on the edge of the PTFE membrane, and epoxy resin glue was used for fixation; a PDMS prepolymer with a thickness of 1 mm (prepolymer to curing agent mass ratio of 10:1) was coated on the surface of the PZT to form a PZT-PDMS packaging layer; an external high-frequency signal generator was connected, and the vibration frequency was set to 20 kHz and the voltage was set to 50 V; the ultrasonic vibration was triggered during self-cleaning, and the vibration frequency was set to 20 kHz, the voltage was set to 50 V, and the duration was set to 30 seconds;
[0054] S6: The above-mentioned PTFE-based membrane, ZrO2-QCS composite layer, Fe3O4 layer and PZT-PDMS packaging layer were laminated in turn, and were fixed by hot pressing; the hot pressing temperature was set to 140°C, the pressure was set to 0.4 MPa, and the time was set to 20 seconds; finally, the filter membrane was immersed in a pH 7.0 phosphate buffer (PBS) for 24 h.
[0055] Example Two:
[0056] This example is basically the same as example one, the difference is that in the step of S3, the mass ratio of chitosan and EPTAC is changed from 1:3 to 1:2, other conditions remain unchanged.
[0057] Example three:
[0058] This example is basically the same as example one, the difference is that in the step of S3, the mass ratio of chitosan and EPTAC is changed from 1:3 to 1:2.5, other conditions remain unchanged.
[0059] Example four:
[0060] This example is basically the same as example one, the difference is that in the step of S3, the mass ratio of chitosan and EPTAC is changed from 1:3 to 1:3.5, other conditions remain unchanged.
[0061] Example five:
[0062] This example is basically the same as example one, the difference is that in the step of S3, the mass ratio of chitosan and EPTAC is changed from 1:3 to 1:4, other conditions remain unchanged.
[0063] Example six:
[0064] This example is basically the same as example one, the difference is that in the step of S3, the mass ratio of chitosan and EPTAC is changed from 1:3 to 1:5, other conditions remain unchanged.
[0065] Example seven:
[0066] This example is basically the same as example one, the difference is that in the step of S4, the molar ratio of FeCl3·6H2O and FeSO4·7H2O is changed from 2:1 to 1.8:1, other conditions remain unchanged.
[0067] Example eight:
[0068] This example is basically the same as example one, the difference is that in the step of S4, the molar ratio of FeCl3·6H2O and FeSO4·7H2O is changed from 2:1 to 2.2:1, other conditions remain unchanged.
[0069] Example nine:
[0070] This example is basically the same as example one, the difference is that in the step of S4, the molar ratio of FeCl3·6H2O and FeSO4·7H2O is changed from 2:1 to 2.5:1, other conditions remain unchanged.
[0071] Comparative example one:
[0072] The comparative example is basically the same as example one, the difference is that step S3 chitosan quaternization reaction and spraying step are omitted, ZrO2-QCS composite layer is not constructed, only ZrO2 functional layer is reserved; the rest of the steps are the same as example one.
[0073] Comparative example two:
[0074] The comparative example is basically the same as example one, the difference is that step S4 does not add Fe3O4 layer, the preparation and deposition steps of Fe3O4 nanoparticles in S4 are omitted, and the rest of the steps are the same as example one.
[0075] Experiment one:
[0076] The influence of the mass ratio of chitosan to EPTAC in different step S3 and the molar ratio of FeCl3·6H2O to FeSO4·7H2O in step S3 on the performance of free pertechnetate adsorption of the filter membrane is evaluated.
[0077] Experimental materials:
[0078] Filter membrane samples: examples one to nine and comparative examples one and two;
[0079] Pertechnetate-containing radioactive solution (about 10 μCi / mL);
[0080] PBS buffer (pH 7.0) radioactivity counter;
[0081] Gamma counter;
[0082] Ultrasonic cleaning system;
[0083] UV-visible spectrometer.
[0084] Experimental steps and methods:
[0085] A1: Pertechnetate removal rate determination;
[0086] Take 5 mL of pertechnetate-containing solution and add it to the filter device, perform gravity filtration under normal pressure, collect the filtrate and measure its radioactivity intensity (CPS), also measure the original solution as a control, and calculate the removal rate:
[0087]
[0088] A2: Self-cleaning efficiency test;
[0089] Filter the mixture containing pertechnetate and protein impurities, measure the initial flux (mL / min), trigger the ultrasonic vibration of the PZT-PDMS layer (20 kHz, 50 V, 30 s), measure the flux again, and calculate the flux recovery rate:
[0090]
[0091] A3: Fe3O4 catalytic reduction ability detection;
[0092] The filter membrane was immersed in PBS containing trace pertechnetate, and reacted for 2 h. The solution was collected and the residual ion concentration was determined by ICP-MS or ultraviolet spectrophotometry, and then the reduction and precipitation rate was calculated:
[0093]
[0094] A4: Long-term stability test;
[0095] The filter membrane was immersed in pH 7.0 PBS, and was taken out at 24 h, 48 h and 72 h, respectively, to observe whether the functional layer was detached, and the surface morphology change was observed by SEM.
[0096] Table I:
[0097]
[0098] From Table I, it can be seen that:
[0099] Example one performs best in pertechnetate removal rate, reaching 98.47%, which is significantly higher than all other examples and comparative examples, among which the removal rates of example four and example eight are 97.93% and 98.12% respectively, which are close to example one, but still slightly lower, and with further deviation of the mass ratio of chitosan to EPTAC or excessive adjustment of the molar ratio of FeCl3·6H2O to FeSO4·7H2O, such as example two (96.32%), example five (96.78%), example six (95.64%) and example nine (96.90%), the removal rates all decrease to different degrees, indicating that the changes of S3 and S4 parameters directly affect the adsorption capacity of ZrO2-QCS layer to free pertechnetate, and especially the combination of chitosan:EPTAC=1:3 and FeCl3·6H2O to FeSO4·7H2O=2:1 is most conducive to realizing the dual mechanism of efficient electrostatic adsorption and coordination bonding, and comparative example one (72.16%) and comparative example two (61.24%) have a significant decrease in adsorption performance due to the lack of QCS coating and Fe3O4 layer respectively, further verifying the key role of the two layers in the adsorption process.
[0100] In terms of self-cleaning efficiency, example one also performs best, reaching 92.31%, which indicates that the matching of its PDMS-PZT packaging layer and the overall structure is optimal, which can efficiently respond to external ultrasonic vibration and effectively remove surface pollutants, and example eight (92.14%) follows closely, showing that appropriately increasing the Fe 3+ / Fe 2+The molar ratio did not significantly affect the self-cleaning performance, but Examples Five (90.27%), Six (89.36%) and Nine (91.28%) had lower flux recovery rates due to decreased adhesion of the functional layer or unstable structure, indicating that changes in spraying parameters and deposition conditions affect the membrane surface density and responsiveness. Comparative Example Two was only 65.39%, much lower than the other groups, indicating that the absence of the Fe3O4 layer not only weakens the catalytic reduction ability, but also reduces the overall responsiveness and stability of the filter membrane.
[0101] At Tc 4+ In terms of precipitation rate, Example One was 63.25%, slightly higher than Example Eight's 63.47%, both of which were basically equivalent, but significantly better than the other groups, indicating that Fe3O4 nanoparticles synthesized under the condition of FeCl3·6H2O and FeSO4·7H2O = 2:1 had the best Fenton-like reaction activity, could more effectively reduce residual technetium ions to insoluble precipitates, thereby achieving a third interception mechanism. Examples Seven (61.33%), Nine (60.85%) and other groups had decreased catalytic performance due to the deviation of the molar ratio from the optimal range, and Example Six and the following groups were significantly weakened. Comparative Example Two was only 12.57%, almost no precipitation effect, further proving the irreplaceable role of the Fe3O4 layer in the reduction reaction.
[0102] In the long-term stability test, Example One showed no shedding after 72 hours of immersion in PBS buffer, indicating that the combination between its functional layers was tight, and the heat pressing solidification process, the use of cross-linking agent, and the selection of materials all achieved the best balance. Examples Five and Nine only had a small amount of shedding, and Example Six had a significant shedding, indicating that when the QCS spraying is too thick or the Fe3O4 deposition is uneven, it will affect the adhesion between the layers. Examples Two to Four, Seven, and Eight remained stable, indicating that adjusting the parameters within a reasonable range would not damage the structural integrity. Comparative Examples One and Two lacked key functional layers, resulting in insufficient interlayer adhesion, and both showed significant shedding after 72 hours, severely affecting the actual application potential.
[0103] In summary, Example One was superior to the other groups in all four core performance indicators, fully demonstrating its comprehensive advantages in adsorption efficiency, self-cleaning ability, catalytic reduction performance, and structural stability, and verifying that the mass ratio of chitosan to EPTAC in S3 and the mass ratio of Fe 3+ / Fe 2+ The parameter combination of a molar ratio of 2:1 was the optimal solution, simultaneously constructing a ZrO2-QCS composite layer and a Fe3O4 catalytic layer, achieving a three-fold efficient interception mechanism of "electrostatic adsorption + coordination bonding + precipitation reduction", and ensuring structural stability and reusability through heat pressing and PDMS packaging.
[0104] The above is based on the ideal embodiment of the application, through the above description, relevant personnel can make various changes and modifications without deviating from the technical idea of the application. The technical scope of the application is not limited to the content of the specification, and the technical scope must be determined according to the scope of claims.
Claims
1. A method for preparing a self-cleaning radiopharmaceutical filter membrane, characterized in that, Includes the following steps: S1: Place the porous PTFE membrane in an oxygen plasma cleaner to generate surface hydroxyl groups. Immerse the activated membrane in a 0.5-2% PVP aqueous solution for 5-15 minutes to allow PVP to be uniformly adsorbed onto the membrane surface. Then dry it at 40-80℃ for 2-3 hours to form a PTFE base membrane. S2: Disperse ZrO2 nanoparticles in anhydrous ethanol and sonicate for 15-60 min to prepare a dispersion. Load ZrO2 onto the surface of a PTFE membrane by impregnation. Stir magnetically at 40-80℃ for 5-7 h. Finally, vacuum dry and cure at 80-160℃ for 1-2 h to form a uniform ZrO2 layer. S3: Chitosan and EPTAC are reacted at 70-90℃ for 18-30h to generate QCS. Unreacted reagents are removed using a dialysis bag with a molecular weight cutoff of 10,000 Da. QCS powder is obtained by freeze drying. QCS is dissolved in water to prepare a 1-3% solution, which is then sprayed onto the surface of the ZrO2 layer and cross-linked with glutaraldehyde solution to form a ZrO2-QCS composite layer. S4: Dissolve FeCl3·6H2O and FeSO4·7H2O in water at a molar ratio of 1.8-2.2:1, adjust the pH to 10.5-11.5 at 80-90℃, stir to generate Fe3O4 nanoparticles, deposit the Fe3O4 suspension onto the surface of the QCS layer through vacuum filtration to form a dense layer with a thickness of 4-6μm, and then dry at 50-70℃ for 1-2h to solidify the Fe3O4 layer; S5: Attach 8-12mm diameter PZT sheets symmetrically at the edge of the PTFE membrane and fix them with epoxy resin. Coat the PZT surface with a 0.8-1.2mm thick polydimethylsiloxane (PDMS) layer to form a PZT-PDMS encapsulation layer. Then connect an external high-frequency signal generator to trigger ultrasonic vibration. During self-cleaning, the PZT drives the PDMS layer to generate ultrasonic waves, combined with the catalytic effect of Fe3O4. S6: Laminate the PTFE base membrane, ZrO2-QCS composite layer, Fe3O4 layer and PZT-PDMS encapsulation layer sequentially, fix them using a hot pressing method, and finally immerse the filter membrane in pH 7.0 PBS buffer for equilibration for 20-30 hours.
2. The method for preparing a self-cleaning radiopharmaceutical filter membrane according to claim 1, characterized in that: In S1, the PTFE membrane has a pore size of 0.22 μm, a thickness of 100 μm, and a porosity of 80%. The oxygen flow rate of the oxygen plasma cleaner is in the range of 30-60 sccm, the power is in the range of 80-150 W, and the processing time is in the range of 3-10 min.
3. The method for preparing a self-cleaning radiopharmaceutical filter membrane according to claim 1, characterized in that: In S2, the ZrO2 nanoparticles have a particle size of 20-50 nm, the dispersion concentration ranges from 5-15 mg / mL, and the impregnation is performed 2-3 times.
4. The method for preparing a self-cleaning radiopharmaceutical filter membrane according to claim 1, characterized in that: In S3, the degree of deacetylation of chitosan is not less than 85%, and the mass ratio of EPTAC to chitosan is 1:1 to 1:
6.
5. The method for preparing a self-cleaning radiopharmaceutical filter membrane according to claim 1, characterized in that: In S3, QCS spraying is performed with a spray gun pressure of 0.2-0.5 MPa, a spraying distance of 10-15 cm, a spraying rate of 0.5-1.0 mL / min, crosslinking with 2-5% glutaraldehyde solution for 1-2 h, followed by rinsing with water 3-5 times.
6. The method for preparing a self-cleaning radiopharmaceutical filter membrane according to claim 1, characterized in that: In S4, the Fe3O4 nanoparticles have a particle size range of 100-200 nm and a magnetic response intensity greater than 50 emu / g.
7. The method for preparing a self-cleaning radiopharmaceutical filter membrane according to claim 1, characterized in that: In S4, the concentration of Fe3O4 suspension ranges from 10 to 20 mg / mL, the vacuum filtration pressure ranges from 0.05 to 0.1 MPa, and the time ranges from 10 to 30 min.
8. The method for preparing a self-cleaning radiopharmaceutical filter membrane according to claim 1, characterized in that: In S5, the thickness of the PZT sheet ranges from 0.5 to 1.0 mm, and the mass ratio of PDMS prepolymer to curing agent is 11:1 to 9:
1.
9. The method for preparing a self-cleaning radiopharmaceutical filter membrane according to claim 1, characterized in that: In S5, the vibration frequency range of the high-frequency signal generator is 15-30 kHz, the voltage range is 20-80 V, the ultrasonic vibration frequency range during self-cleaning is 15-25 kHz, the voltage range is 40-60 V, and the trigger time range is 10-60 s.
10. The method for preparing a self-cleaning radiopharmaceutical filter membrane according to claim 1, characterized in that: In S6, the hot pressing temperature range is 120-160℃, the hot pressing pressure range is 0.2-0.6MPa, and the hot pressing time is 10-30s.
